Individuals’ Knowledge of Cardiovascular Diseases Determination of Levels and Behaviors - ERMİŞ, Zeliha (MAS Journal of Applied Sciences, 2024)
It is assumed that having information about the risk factors of cardiovascular diseases is an important element in the prevention of cardiovascular diseases. This study was conducted as a descriptive study to determine the relationship between individuals’ knowledge about cardiovascular disease risk factors and their behavior patterns. 702 people participated in the research. The data were collected using the Participant Information Form and the Cardiovascular Disease Risk Factors Knowledge Level Scaling (KARRIF-BD). It was found that the participants had a moderate level of cardiovascular disease knowledge. It was determined that the knowledge levels of smokers were lower than those who did not use cigarettes. It was determined that the knowledge levels of those who preferred not to eat fast food products were higher than those who preferred to eat. Effective educational programs should be organized and awareness should be created in order to acquire healthy lifestyle behaviors that play an important role in protecting individuals from cardiovascular diseases.